Platelets and Metastasis: New Implications of an Old Interplay - Lucotti, Serena; Muschel, Ruth J. (Frontiers in Oncology, 2020)
During the process of hematogenous metastasis, tumor cells interact with platelets and their precursors megakaryocytes, providing a selection driver for the metastatic phenotype. Cancer cells have evolved a plethora of mechanisms to engage platelet activation and aggregation. Platelet coating of tumor cells in the blood stream promotes the successful completion of multiple steps of the metastatic cascade. Along the same lines, clinical evidence suggests that anti-coagulant therapy might be associated with reduced risk of metastatic disease and better prognosis in cancer patients. Here, we review experimental and clinical literature concerning the contribution of platelets and megakaryocytes to cancer metastasis and provide insights into the clinical relevance of anti-coagulant therapy in cancer treatment.